Under the IOT Platform a Novel Algorithm for Minimization of Current Pulsation in PFC Circuit - Wenwen Zhang; Lei Wang; Peilong Li; Lihua Ye; Zhiming Hu; Hongtao Xiang (IEEE Access, 2018)
In order to achieve the IOT, in the traditional one-cycle controlled PFC circuit, the system's switching losses considerably increase with the control switching frequency and the system's power, severely affecting the system's efficiency. In order to address this problem, an improved one-cycle hysteresis controlling circuit is proposed in this paper. An improved one-cycle controlled PFC circuit is also proposed to minimize the input current pulsation. The duty ratio of the output-control power switching tube is computed in real-time by computing the rate of rise and fall of the current in the input inductance. The next current sampling point is computed in real-time based on the duty ratio of each switching period. A simulation model and 152VA prototype are established via Matlab, Simulation, and test results of the prototype demonstrate the correctness and feasibility of the proposed one-cycle hysteretic control circuit and the current pulsation minimization algorithm.